Damping of electron density Rabi-oscillations and self-induced-transparency in semiconductor quantum dots - Förstner, Jens; Weber, C.; Danckwerts, J.; Knorr, A. (Postconference Digest Quantum Electronics and Laser Science, 2003. QELS.)
A non-Markovian quantum kinetic theory of the coupled electron-phonon system in semiconductor quantum dots is used to analyze the nonlinear dipole decoherence and light propagation dynamics for arbitrary pulse strengths and lengths.
Keywords: tet_topic_qd

Correlated influence of carrier-carrier/carrier-phonon interaction and radiative damping on semiconductor intersubband transitions - Waldmuller, I.; Förstner, Jens; Knorr, A.; Woerner, M.; Reimann, K.; Kaindl, R.A.; Hey, R.; Ploog, K.H. (Postconference Digest Quantum Electronics and Laser Science, 2003. QELS.)
The linewidth of intersubband transitions resulting from simultaneous action of many-body contributions and radiative damping is analyzed. The processes are non-additive and a self-consistent treatment is necessary to explain recent experiments.
Keywords: tet_topic_qw

Self-induced transparency in InGaAs quantum dot waveguides - Schneider, S.; Borri, P.; Langbein, W.; Woggon, U.; Förstner, Jens; Knorr, A.; Sellin, R. L.; Ouyang, D.; Bimberg, D. (physica status solidi (c))
We present the experimental observation and the theoretical modelling of self-induced transparency signatures such as nonlinear transmission, pulse retardation and reshaping for subpicosecond pulse propagation in a 2 mm-long InGaAs quantum-dot ridge waveguide at 10 K. The measurements were obtained using a cross-correlation frequency resolved optical gating technique which allows us to retrieve the field amplitude of the propagating pulses.
Keywords: tet_topic_qd

Gewinn- und Kapitalbeteiligungen in britischen, französischen und deutschen Unternehmen: Eine institutionalistisch orientierte empirische Untersuchung - Kabst, Rüdiger; Matiaske, W; Schmelter, A (Zeitschrift für Personalforschung.)

Online Marktforschung im Mittelstand: Analyse von Konsumentenverhalten in 3D-Internet-Welten - Schryen, Guido; Herstell, Jan; Schoenen, Markus

Online-Marktforschung - Analyse von Konsumentenverhalten in virtuellen Umgebungen, in: Information Management & Consulting, 18,2 - Schryen, Guido; Herstell, Jan (IM : die Zeitschrift für Information Management und Consulting)

E-Democracy: Internet Voting - Schryen, Guido (Proceedings of the IADIS International Conference WWW Internet 2003. vol. 2)
Voting via the Internet is part of electronic government and electronic democracy. However, there are many obstacles which have to be overcome, especially legal restrictions have to be transformed into technical and security solutions. In the first part the article discusses advantages and disadvantages of Internet elections, shows different application fields, and presents important international pilot schemes (political and business ones). in the second part, due to democratic basic principles, technological security aspects are worked out.
Keywords: Internet Voting; Online polls; E-Democracy; Security

Internet-Wahlen - Schryen, Guido (6. Internationale Tagung Wirtschaftsinformatik)
Zusammenfassung: Im Rahmen des E-Governments werden zunehmend Internetwahlen diskutiert. Der Beitrag diskutiert zunächst die Vor- und Nachteile derartiger Wahlen und zeigt Anwendungsgebiete sowie durchgeführte Pilotprojekte im politischen wie auch wirtschaftlichen Bereich auf. Im Rahmen eines Anforderungssystems werden anschließend aus demokratischen Wahlgrundsätzen sicherheitstechnologische Anforderungen herausgearbeitet. Zu deren Adressierung werden kryptographischen Wahlkonzepte herangezogen, von denen die wichtigsten vorgestellt werden. Aufgrund der Komplexität der Anforderungslandschaft wird ein sicherheitstechnologisches Strukturmodell vorgestellt, das insbesondere dazu dient, die Sicherheit(skomponenten) eines Wahlsystems systematisch mit den Anforderungen abzugleichen. Der Artikel schließt mit einem Ausblick auf notwendige Untersuchungen.
Keywords: Internet-Wahlen; E-Democracy; Sicherheit; Kryptographie

Planspiel Marmelade - Entwicklung und Implementation - Kennerknecht, M.; Kremer, H.-Hugo (Institutionelle Perspektiven beruflicher Bildung (Meilensteine der beruflichen Bildung))

Handlungs- und Fachsystematik im Lernfeldkonzept - Kremer, H.-Hugo (bwp@ Ausgabe Nr. 4)